2009
DOI: 10.1016/j.neuroscience.2009.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Partial ablation of mu-opioid receptor rich striosomes produces deficits on a motor-skill learning task

Abstract: Basal ganglia striosomes, or patches, are rich in mu opioid receptors (MOR) and form a 3-dimiensional labyrinth of cells that extend throughout the mid and anterior striatum in mice. Though previous studies have suggested that striosomes could affect drug-induced motor output in rodents, the functional role of these compartmentalized MOR-rich striosomes is not well understood. To investigate any relationship between the striosomes and motor behavior we used the toxin dermorphin-saporin (DS) to selectively abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 50 publications
3
20
0
Order By: Relevance
“…Thus, patch and matrix compartments are proposed to operate as independent and functionally separate microcircuits with distinct inputs, local circuitry, and outputs. These anatomical relationships are consistent with the implication of patches in experience-based locomotor learning and reward-guided behavior (Canales and Graybiel, 2000; Friedman et al, 2015; Lawhorn et al, 2009; White and Hiroi, 1998). …”
Section: Introductionsupporting
confidence: 82%
“…Thus, patch and matrix compartments are proposed to operate as independent and functionally separate microcircuits with distinct inputs, local circuitry, and outputs. These anatomical relationships are consistent with the implication of patches in experience-based locomotor learning and reward-guided behavior (Canales and Graybiel, 2000; Friedman et al, 2015; Lawhorn et al, 2009; White and Hiroi, 1998). …”
Section: Introductionsupporting
confidence: 82%
“…However, our group and others have previously shown that both the matrix compartment and cholinergic interneurons were unaffected following DERM-SAP treatment (Lawhorn et al, 2009; Murray et al, 2014). In addition, following DERM-SAP treatment, roughly 30% of mu opioid receptor-labeled patches remained intact, which could explain why there was not a complete abolishment of stereotypy following repeated COC treatment and challenge.…”
Section: Discussionmentioning
confidence: 73%
“…In order to address the role of the patch compartment of rostral striatum in the expression of stereotypy following repeated COC treatment, we utilized the neurotoxin dermorphin-saporin (DERM-SAP (Lawhorn et al, 2009; Murray et al, 2014; Tokuno et al, 2002); to specifically ablate the neurons that comprise the rostral patch compartment prior to exposure to COC. Mu opioid receptors are densely expressed by the neurons of the patch compartment, while the neurons of the matrix compartment contain relatively few mu opioid receptors (Herkenham and Pert, 1981; Pert et al, 1976; Tempel and Zukin, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…While the function of the patch and matrix compartments has not been clearly determined, studies suggest roles in motor learning (Canales and Graybiel, 2000; Lawhorn et al, 2009), reward-guided learning (White and Hiroi, 1998) and biasing decisions during cost-benefit conflict (Friedman et al, 2015). Furthermore, patch/matrix are differentially affected in neurological pathologies such as Parkinson’s disease (Koizumi et al, 2013), Huntington’s disease (Lawhorn et al, 2008), drug addiction (Hurd and Herkenham, 1993), and others (Crittenden and Graybiel, 2011).…”
Section: Introductionmentioning
confidence: 99%